Entrepreneurship as a Competitive Development of Vocational Education: Theory and Practice - A. G. Mokronosov; I. N. Mavrina (Russian State Vocational Pedagogical University, 2015)
The paper considers the complex of economic processes in the sphere of the higher vocational education. The research is aimed at investigating, clarifying and systemizing the theoretical concepts of entrepreneur- ship in the context of the knowledge economy and rising competitiveness in the market of scientific and educational services. The research methodology basis involves the works of domestic and foreign scholars in the fields of competitive development, entrepreneurship, quasi-markets theories and self- developing organizations. The paper presents the author's interpretation of the university entrepreneurship as the integrated and systematic process generated by the dramatic changes of socio-economic development, increasing global trends of economy intellectualization, significant proportion of scientific and educational services, and increasing role of modernization in sustaining the state welfare and stability. The university entrepreneurship is regarded as a synthesis of creative, innovative, commercial and managerial activities in the market of scientific and educational services, labor market, industrial and financial markets. The interrelation of economic and social aspects of university business is revealed including the links between the government, universities, scientific educational institutions, business community, households and other subjects of educational service market. The application of the main theoretical principles of the research concerning the higher school business vector is demonstrated by the practical activity of the Russian Vocational Pedagogical University.